1998
DOI: 10.1046/j.1464-410x.1998.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence of prostate cancer with selenium supplementation: results of a double‐blind cancer prevention trial

Abstract: Objective  To test if supplemental dietary selenium is associated with changes in the incidence of prostate cancer. Patients and method  A total of 974 men with a history of either a basal cell or squamous cell carcinoma were randomized to either a daily supplement of 200 μg of selenium or a placebo. Patients were treated for a mean of 4.5 years and followed for a mean of 6.5 years. Results  Selenium treatment was associated with a significant (63%) reduction in the secondary endpoint of prostate cancer incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
308
4
13

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(338 citation statements)
references
References 20 publications
13
308
4
13
Order By: Relevance
“…Two of them are based on the measurement of the long-term selenium intake using toe-nail clippings, 3,6 one is based on serum selenium measurements, 5 and one on selenium supplementation in a double-blinded study. 2 Three studies reported a reduction of risk for developing prostate cancer as the selenium level increased, suggesting that selenium can provide a two -three-fold protection against prostate cancer. One study showed an association only in smokers, 5 and one study failed to find any significant association between toe-nail selenium level and the risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them are based on the measurement of the long-term selenium intake using toe-nail clippings, 3,6 one is based on serum selenium measurements, 5 and one on selenium supplementation in a double-blinded study. 2 Three studies reported a reduction of risk for developing prostate cancer as the selenium level increased, suggesting that selenium can provide a two -three-fold protection against prostate cancer. One study showed an association only in smokers, 5 and one study failed to find any significant association between toe-nail selenium level and the risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clark and colleagues 2 found striking evidence that selenium supplementation protected men against prostate cancer in a randomised trial in the USA (OR: 0.35; CI: 0.18 -0.65). Another study has revealed an inverse association between advanced prostate cancer and toe-nail selenium levels, a surrogate marker of long-term selenium intake.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In general, foods rich in saturated fat and calories are considered as promoters of prostate cancer, 3,4 whereas vegetables and fruits, including selenium, vitamins A, E, D and C, and isoflavones are inhibitors. [5][6][7][8] It is strongly suggested that the recent significant increase in the incidence of prostate cancer, as well as cardiovascular diseases and diabetes mellitus in Japan may be due to the increased habitual consumption of high-calories high-fat food. Nonetheless, the morbidity of prostate cancer among the Japanese is still significantly lower than among the Caucasian, African and Hispanic people.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial in a Western population, significantly lower total cancer incidence and mortality were observed among patients who received selenium compared with patients who did not receive selenium. 8,9 The intervention trials of selenium supplementation in Linxian, China, an area with a high incidence and mortality of esophageal cancer, also revealed reductions in the risk of esophageal cancer. 10,11 Selenium can modulate DNA methylation and cancer susceptibility, [12][13][14][15] and selenium deficiency may induce genetic damage and play an important role in carcinogenesis.…”
mentioning
confidence: 99%